PENGETAHUAN AKUNTANSI PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) ATAS PENGGUNAAN INFORMASI AKUNTANSI - Evi Linawati; MI Mitha Dwi Restuti (Conference In Business, Accounting, And Management (CBAM), 2015)
In order to encourage small businesses to conduct and use of accounting information, needs to start from the small entrepreneur's knowledge of the accounting information. knowledge of SME entrepreneurs on accounting information is also determined by their experience in organizing and using accounting information. The purpose of this study for to determine how much influence accounting knowledge micro, small and medium on accounting information. The data used is primary data obtained through questionnaires to the owners of SMEs. The population in this study were all industrial convection in District Tingkir Salatiga. The sampling method used in this research is purposive sampling with 60 owners of SMEs. Analysis tools using descriptive statistics and regression analysis using simple tools. The results showed that the perception does not affect the accounting information while hadil indicates that accountancy What Knowledge affect the accounting information on SMEs Convection in District Tingkir Lor Salatiga. Keywords: knowledge of accounting, accounting information and SME